Family Communication Literacy Education and Social Marketing in Health Center West Java Indonesia - Erlina Puspitaloka Mahadewi; Suryari Purnama; Fachmi Tamzil; Intan Silviana Mustikawati; Mohamad Reza Hilmy; Dwi Nurmawaty (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The present study reports study after pandemic era for family communication literacy and social marketing activities carried out by cadres in promoting the Kenanga Depok posyandu program, in West Java, Indonesia. Posyandu which is a form of Community-Based Health Efforts is managed and organized by, for, and with the community. In the context of carrying out health development, by empowering the community and providing opportunities for the community to receive basic health services. It has a goal to reduce maternal and child mortality. Becomes interesting to describe the social marketing activities of posyandu cadres as the spearhead of the national health program. This study uses a qualitative approach with a case study method and data collection techniques in the form of in-depth interviews. Theories used in this study include health communication theory and social marketing. Meanwhile, secondary data was obtained from posyandu documents and research notes during field observations. The results of this study indicate that posyandu cadres use health promotion strategies that are persuasive, educative, and innovative. This persuasive effort is shown through the intensive mentoring strategies and direct socialization styles according to the target context. Posyandu cadres also involve experts from the puskesmas and the community to play an active role in improving the quality of the posyandu program in their environment. As for the educational aspect, it is shown by the efforts of posyandu cadres which lead to the empowerment of posyandu participants in paying attention to the growth and development of children. The conclusion is that the posyandu program carried out by the cadres is in accordance with real conditions to create changes in the behavior of the posyandu participating community through communication literacy education activities in the family and social marketing that are persuasive, educative, and innovative.